Kontribusi Besar Pendapatan Wanita Pemulung terhadap Pendapatan Keluarga (Studi Kasus pada Wanita Pemulung di TPA Gunung Tugel Kabupaten Banyumas) - Dijan Rahajuni; Endang Sri Gunawati; Irma Suryahani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
The Purposes of this study are to determine the contribution of woman rollers garbage’s income toward income of family, degree of poverty, and degree of welfare on the rollers garbage’s family. A respondent on this study are women rollers garbage that have already married and have children with the amount as many as 25 percent or 22 person of woman rollers garbage. The tool of analysis that used are tabulation for determine contribution of income, double linear regression to determine factors that influence toward income and income ratio with the poverty line from the result of Statistics Central Department (BPS) on 2007 to recognize degree of poverty and to determine degree of welfare’s ratio income with the needed of dialy life on October 2008 in Banyumas regency. The results of study show that: a. Contribution of woman roller garbage’s income toward income of family, is included in the big scale with the 61.98% average.b. The result of F-test and t-test in factors of : age, education, experience for rolling garbage and the amount of children, have significant toward income of roller garbage. Which the rank is from the biggest influenced of them are the amount of children, education, age and experience for rolling garbage.c. Average degree of welfare of rollers garbage family is stated above absolutes poverty line as 155.58%d. But however degree of welfare of woman roller garbage’s family is still under the welfare, its still reach 33.25 percent.From that study, implication appears toward the rollers garbage, they should be increase their creativity and toward other side of rollers garbage should be provide the different place of organic garbage and non organic one on TPA, and also give such kind of health service and creativity education. Keywords: woman rollers garbage, income